Kejawen modern : hakikat dalam penghayatan Sumarah - Stange, Paul, 1947- (Yogyakarta : Penerbit & distribusi, LKiS Yogyakarta, 2009)
On Paguyuban Sumarah, a spiritual movement in Indonesia, and its concept on Javanese mysticism towards modernization era.
Includes bibliographical references (p. 367-380) and index.
Keywords: Paguyuban Sumarah; Mysticism -- Indonesia -- Java